PEMIKIRAN PENDIDIKAN PESANTREN K.H. HASYIM ASYARI DAN PENGEMBANGAN ISLAM BERBASIS MULTIKULTURAL DI INDONESIA - Moh Yusuf (TANZHIMUNA : Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to examine the educational thoughts of K.H. Hasyim Asy’ari regarding pesantren (Islamic boarding schools) and their relevance to the development of multicultural-based Islam in Indonesia. As a prominent Islamic scholar and the founder of Nahdlatul Ulama, K.H. Hasyim Asy’ari made significant contributions to shaping the pesantren education system grounded in Islamic values, nationalism, and openness to cultural diversity. This research employs a qualitative-descriptive approach through library research. The findings reveal that K.H. Hasyim Asy’ari’s educational philosophy emphasizes the importance of moral character, mastery of religious knowledge, and a tolerant attitude toward differences. Pesantren are positioned not only as institutions for producing religious scholars but also as spaces for character-building that enable students to live harmoniously in a pluralistic society. Thus, the pesantren values inspired by K.H. Hasyim Asy’ari are highly relevant in strengthening social integration and supporting the development of multicultural Islam in Indonesia.